Application Investigation of a Hydroxylammonium Nitrate Thermocatalytic Thruster on "Green Propellant". (2017) - Goza, D.A.
Abstract: A transition from hydrazine to less environmentally hazardous monopropellants with higher specific characteristics is considered to be perspective for thermocatalytic thrusters which are used for spacecraft attitude control and station keeping. Such propellants are commonly named as "green propellants". Hydroxylammonium nitrate can be used as a basis for such a propellant. Hydroxylammonium nitrate-based propellant has a higher density, higher specific impulse and a lower freezing temperature compared to hydrazine. The high combustion temperature of the propellant (above 1800 0 С) and strong oxidation properties of the combustion products impose specific requirements to the thruster design materials used. A laboratory model of the К100E thruster has been developed. The product operating capability with high dynamic characteristics has been demonstrated.